Pengaruh Brand Image dan Kualitas Produk terhadap Loyalitas Pelanggan Dimediasi Kepuasan terhadap Produk MS Glow di Kabupaten Tebo - Fina Sari (JURNAL RISET MANAJEMEN (JURMA), 2024)
This research aims to determine and analyze the influence of Brand Image and Product Quality on Customer Loyalty with Satisfaction as an intervening variable on MS Glow Skincare Products at Elena Beauty Store in Tebo Regency. The population in this study is unlimited, and the sample in this study consists of 100 respondents. The sampling technique used is Accidental Sampling. The results of the research analysis indicate that Brand Image has a positive and significant effect on consumer satisfaction with MS Glow skincare products at Elena Beauty Store. Product Quality has a positive and significant effect on consumer satisfaction with MS Glow skincare products at Elena Beauty Store. Furthermore, Brand Image has a positive and significant effect on customer loyalty to MS Glow skincare products at Elena Beauty Store in Tebo Regency. Product Quality has a positive and significant effect on customer loyalty to MS Glow skincare products at Elena Beauty Store in Tebo Regency. Consumer satisfaction has a positive and significant effect on customer loyalty to MS Glow skincare products at Elena Beauty Store in Tebo Regency. Brand Image and Product Quality have a positive and significant effect on Customer Loyalty, mediated by Satisfaction with MS Glow skincare at Elena Beauty Store in Tebo Regency.